Digitalisasi Koperasi Sebagai Upaya Meningkatkan Efektivitas Pelayanan - Paulus Paulus (FOKUS : Publikasi Ilmiah untuk Mahasiswa, Staf Pengajar dan Alumni Universitas Kapuas Sintang., 2026)
The development of information and communication technology has encouraged cooperative institutions to transform their service systems to remain competitive and relevant in the digital era. Many cooperatives still experience limitations in administrative management, transaction recording, and service delivery due to manual systems. This study aims to analyze cooperative digitalization as an effort to improve service effectiveness. The research employed a descriptive qualitative approach involving cooperative managers, employees, and members as research subjects. Data were collected through interviews, observations, and documentation. Data analysis was conducted through data reduction, data presentation, and conclusion drawing. The results indicate that cooperative digitalization has been implemented through information system utilization in managing membership data, financial transactions, and service delivery. Digitalization contributes to improving service effectiveness, particularly in service speed, data accuracy, service accessibility, and transparency of cooperative management. Members can access financial information and conduct transactions more efficiently through digital systems. However, several challenges remain, including limited human resource competencies, inadequate technological infrastructure, and member adaptation to digital services. Therefore, continuous training, infrastructure development, and member education are necessary to optimize digital service implementation. This study concludes that cooperative digitalization is a strategic effort to improve service effectiveness and strengthen cooperative competitiveness in the digital transformation era. Keywords: cooperative digitalization, service effectiveness, digital service.